Penanggulangan Kejahatan Di Bidang Pariwisata Pada Wilayah Hukum Direktorat Pengamanan Objek Vital Kepolisian Daerah Jawa Timur - Rahmanto, Dwi (Universitas Wijaya Putra, 2025)
The government has made efforts to develop the tourism sector through various programs, such as developing priority tourist destinations, training tourism human resources, and tourism promotion. The allocation of PEN funds for tourism and the creative economy shows the government's commitment to supporting the recovery and development of this sector. Tourism has an important role in supporting the national economy towards Advanced Indonesia 2024. This sector has great potential to drive economic growth, open up jobs, and improve people's welfare. With government support and joint efforts, tourism can become one of the main drivers of the national economy. This study aims to provide answers regarding the effectiveness and role of the Tourism Police in overcoming crime in the tourism sector in East Java Province. From the results of the study, it can be concluded that reducing security disturbances in securing vital tourism objects will be able to provide a sense of security for travelers so that both foreign and domestic tourists feel safe and comfortable in carrying out their tourism activities. In the long term, high security standards in East Java Province are expected to be able to drive the world-class tourism sector, become the main destination for world tourism after Bali, and can boost the economy of Surabaya in particular and East Java in general. The role of the Tourism Police of the Directorate of Vital Object Security of the East Java Regional Police is very important in maintaining the security and comfort of tourists in East Java expected to be able to drive the world-class tourism sector, become the main destination for world tourism after Bali, and can boost the economy of Surabaya in particular and East Java in general. The role of the Tourism Police of the Directorate of Vital Object Security of the East Java Regional Police is very important in maintaining the security and comfort of tourists in East Java Province which is outlined in several of its work programs so that it is concluded that its performance has been effective, although there are still obstacles such as a lack of personnel or the need to improve foreign language human resources.